2020
DOI: 10.1248/bpb.b20-00266
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Febrile Neutropenia Induced by Docetaxel Chemotherapy in Patients with Non-small Cell Lung Cancer

Abstract: We retrospectively obtained data of patient background and pretreatment characteristics from medical records and identified the predictive factors of febrile neutropenia (FN) in patients with non-small cell lung cancer (NSCLC) treated with docetaxel alone or in combination with the anti-vascular endothelial growth factor (VEGF) antibody bevacizumab. Patients were eligible for inclusion in the study if they were 20 years or older, diagnosed with NSCLC, and received docetaxel monotherapy alone or in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Similar to the previous studies, 37,38 the absence of platinum use and low haemoglobin levels were associated with higher neutropenia risk. The small number of patients and single center are the major limitations of this study, which may lead to some bias.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the previous studies, 37,38 the absence of platinum use and low haemoglobin levels were associated with higher neutropenia risk. The small number of patients and single center are the major limitations of this study, which may lead to some bias.…”
Section: Discussionsupporting
confidence: 88%
“…34 In our study and in the study by Wang, 35 the median and mean docetaxel AUCs of patients with grade 3/4 neutropenia were 3.3 and 2.8 mg h/L, respectively, whereas the mean docetaxel AUC of European patients was 4.4 mg h/L. 16 Similar to the previous studies, 37,38 the absence of platinum use and low haemoglobin levels were associated with higher neutropenia risk. The small number of patients and single center are the major limitations of this study, which may lead to some bias.…”
Section: Discussionsupporting
confidence: 84%
“…There is no report evaluating factors associated with the overall severe adverse effects inducing treatment reduction in DOC + RAM; however, there are some studies regarding FN in DOC monotherapy. Uchida et al have reported that higher baseline hemoglobin levels could be associated with FN development in patients with NSCLC, although it was not assessed in multivariate analysis owing to the small patient population (unadjusted odds ratio 1.34; 95% confidence interval, 0.99-1.88; P = 0.06) 23 . In contrast, Hirasawa et al and Kwon et al reported that baseline hemoglobin levels are not associated in patients with castration-resistant prostate cancer 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for approximately 85% of lung cancer-related mortality, 9) and early metastasis is the main cause of deaths from the disease. 10,11) Combined with a plastic and responsive microenvironment, random epigenetic and genetic mutations in cancer support the metastatic evolution of tumors. 12) Currently among tested molecular factors in lung cancer patients, differential expression and regulation of microRNA (miRNA) molecules seem to be the most attractive.…”
Section: Introductionmentioning
confidence: 99%